The grapevine SOC1 homolog, VviMADS8/SOC1a, regulates floral organ specification in tomato - Jenna Bryanne Jolliffe; Claudio Moser; Stefania Pilati; Justin Graham Lashbrooke (Fruit Research)
The MADS-box protein SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1 (SOC1) is a key floral activator that coordinates external and internal stimuli to ensure timely floral transition. During early development, SOC1 represses floral organ identity to prevent premature differentiation and, thus, is also linked to the successful development of functional flowers. In woody perennials, SOC1 has established a divergent function in the regulation of bud dormancy release. Apart from reducing flowering time in Arabidopsis, little is known about the function of VviSOC1a and its gene regulatory network. In this study, VviSOC1a was functionally characterized through overexpression in tomato, where it was found to promote the development of leaf-like sepals and petals with an increased accumulation of chlorophyll. In severe cases, overexpression of VviSOC1a led to the formation of defective floral organs resulting in plant sterility phenotypes. Gene expression analyses revealed the significant downregulation of important floral organ identity genes in tomato, such as SIMC, SlRIN, SlCMB1, and SlMBP21. Additional downstream impacts on ripening and cuticle-associated gene expression warrant further characterization of VviSOC1a within the context of these crop traits. In silico analysis of the VviSOC1a expression profile revealed patterns distinctive of genes involved in floral induction. This, in combination with an association gene network significantly enriched in flower developmental processes, supports a predicted function for VviSOC1a in floral initiation and floral organ specification.